KEMAMPUAN NUMBER SENSE MELALUI METODE LEARNING BY PLAYING - Tunjung Susilowati, Tunjung Susilowati (JURNAL PENDIDIKAN DASAR, 2015)
Abstract: One of many purpose on mathematic teaching is problem solving. Problem solving need good computation abilities. Student have computation abilities if numbersense develop in them. Number sense related with flexible and intuitive thinking aboutnumber. Number sense is natural ability of human and developed with teaching. Thisresearch using learning by playing teaching method to develop number sense. Thepurpose of choosing this method is student can practice their number sense andobserved directly also mathematics can be fun subject. Research conducted with usingdifferent kind of games in every session. Based from the research, student developedtheir number sense on addition and subtraction of integers and they enjoy the learningalso. Keywords: Number sense, learning by playing, summation and Equity pbulat numbers.